Professional Bodies and Quality Assurance of Higher Education Programmes in South Africa: Towards an Appropriate Framework - Ballim, Yunus; Mabizela, Sizwe; Mubangizi, John Cantius (South African Journal of Higher Education, 2018)
Collaboration between universities and professional bodies is neither new nor unique to South Africa. It occurs in many higher education systems and revolves around the role that professional bodies play in the quality assurance and accreditation of the relevant higher education programmes. In South Africa, this relationship has become increasingly problematic over the recent past due to a number of factors. This article begins by exploring those factors before highlighting the legal framework governing the role of professional bodies in University programmes. A critique of the said role is then undertaken against the backdrop of views and opinions from academics involved in professional programmes in some South African universities, including the thorny issue of who should meet the costs of accreditation. The article concludes with suggestions on the principles that should underpin a revised framework, under the custodianship of the Council on Higher Education, to govern the relationship between universities and professional bodies.